High temperature and full-in-plane-direction workable high-frequency soft magnetic epitaxial FeSi thin films on MgO(0 0 1). (12th January 2016) - Guo, X B; Wu, K; Cui, B S; Li, D; Yun, J J; Zuo, Y L; Zuo, H P; Wang, T; Xi, L
Abstract: The epitaxial FeSi(0 0 1)[1 1 0]//MgO(0 0 1)[1 0 0] films were fabricated by sputtering and post annealing at 800 °C. A four-fold symmetric angular dependence of remanence ratios and coercivities of FeSi films were observed and well fitted by theoretical models considering the cubic anisotropy. The experimental ferromagnetic resonance frequency ( f r ) of epitaxial FeSi films reaches to 8.0 GHz, which is in agreement with the theoretical value derived from Landau–Lifshitz–Gilbert equation at room temperature. Moreover, the resonance phenomenon can be observed in any in-plane directions in contrast with the absence of resonance phenomenon in some specific directions for in-plane uniaxial soft magnetic Fe2 Co films. Although the saturation magnetization, cubic anisotropy constant and f r all decrease with increasing temperature, f r still can keep as high as 3.2 GHz at 800 K, indicating that the epitaxial FeSi films with high Curie temperature have potential application in full angle workable microwave devices at relatively high temperature.